ANTIOXIDANT ACTIVITY, TOTAL PHENOLIC CONTENT, AND FTIR ANALYSIS OF FERMENTED BADUY HONEY WITH PINEAPPLE - Adri Nora; Anjas Wilapangga; Amenia Kahfi; Meisya Then; Atikah Fairus (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2022)
Honey is one of the liquid foods known for its high nutritional value. Honey contains macronutrient and micronutrient compounds. The composition of honey is usually different from one honey to another and has different biological activities. Baduy honey is one of the forest honey sold by the Baduy tribe. Fermented Baduy honey is suspected of having better biological activity. This study aims to determine the antioxidant activity of fermented Baduy honey, the total phenolic compound, and FTIR analysis. The antioxidant activity was determined against DPPH (2,2-Diphenyl-1-picrylhydrazile) by measuring the absorbance of the sample at the wavelength of 517 nm. The Total phenolic compound was also determined using folin ciocalteu’s method to measure the absorbance of the sample at the wavelength of 765nm. The FTIR analysis was also carried out to detect functional groups in Baduy honey. The antioxidant activity shows that fermented Baduy honey has the highest antioxidant capacity (IC 50 = 90,26 µg/mL) after three days of fermentation with pineapple and has better antioxidant capacity than non-fermentation Baduy honey. Total phenolic content shows that Baduy honey has 2,04 µg/mL. The FTIR analysis result indicates the presence of phenolic compounds, which can be found in flavonoids.